Effect of surfactants on plasmid DNA stability and release from Poly (D, L-lactide-co-glycolide) microspheres - Doolaanea, Abd Almonem; Ismail, Ahmad Fahmi Harun; Mansor, Nur‘Izzati; Nor, Nurul Hafizah Mohd; Mohamed, Farahidah (Pharmacotherapy Group, Faculty of Pharmacy, University of Benin, 2015)
Purpose: To evaluate the effect of surfactants on plasmid DNA during preparation and release from polylactic glycolide (PLGA) microspheres. Methods: Various surfactants, both ionic and non-ionic (Span, Tween, Triton X100, cetyltrimethylammonium bromide and sodium dodecyl sulphate), were added during the microsphere preparation and their effect was evaluated. Supercoil index (SCI) was introduced as a harmonised value derived from encapsulation efficiency and supercoil preservation efficiency in order to evaluate the impact of different surfactants on pDNA encapsulation. Results: Polyvinyl alcohol and Span revealed low SCI whereas Tween increased the SCI in a fraction- dependent manner. The Tween blend of hydrophilic-lipophilic balance (HLB) of 16 and Triton X-100 (HLB = 13.5) showed the highest SCI. Span revealed high burst release of pDNA whereas Triton X-100 exhibited low burst release. Following the burst release, diffusion mechanism was found to predominate in DNA release. Conclusion: The microspheres were non-toxic to the neuro-2a cells which suggest they can be potentially used in the gene therapy of neuronal diseases.